Pharmacological profile of asundexian, a novel, orally bioavailable inhibitor of factor XIa. (25th March 2022) - Heitmeier, Stefan; Visser, Mayken; Tersteegen, Adrian; Dietze‐Torres, Julia; Glunz, Julia; Gerdes, Christoph; Laux, Volker; Stampfuss, Jan; Roehrig, Susanne
Abstract: Background: Activated coagulation factor XI (FXIa) contributes to the development and propagation of thrombosis but plays only a minor role in hemostasis; therefore, it is an attractive antithrombotic target. Objectives: To evaluate the pharmacology of asundexian (BAY 2433334), a small molecule inhibitor targeting FXIa, in vitro and in various rabbit models. Methods: The effects of asundexian on FXIa activity, selectivity versus other proteases, plasma thrombin generation, and clotting assays were evaluated. Antithrombotic effects were determined in FeCl2 ‐ and arterio‐venous (AV) shunt models. Asundexian was administered intravenously or orally, before or during thrombus formation, and with or without antiplatelet drugs (aspirin and ticagrelor). Potential effects of asundexian on bleeding were evaluated in ear‐, gum‐, and liver injury models. Results: Asundexian inhibited human FXIa with high potency and selectivity. It reduced FXIa activity, thrombin generation triggered by contact activation or low concentrations of tissue factor, and prolonged activated partial thromboplastin time in human, rabbit, and various other species, but not in rodents. In the FeCl2 ‐injury models, asundexian reduced thrombus weight versus control, and in the arterial model when added to aspirin and ticagrelor. In the AV shunt model, asundexian reduced thrombus weight when administered before or during thrombus formation. Asundexian alone or in combination with antiplatelet drugs did not increase bleeding times or blood loss in any of the models studied. Conclusions: Asundexian is a potent oral FXIa inhibitor with antithrombotic efficacy in arterial and venous thrombosis models in prevention and intervention settings, without increasing bleeding.